Whole-genome sequencing combined RNA-sequencing analysis of patients with mutations in SET binding protein 1 - Liu, Li; Feng, Xiaoshu; Liu, Sihan; Zhou, Yanqiu; Dong, Xiaojing; Yao, Hong; Tan, Bo (Frontiers in Neuroscience, 2022)
SET binding protein 1 (SETBP1) is essential for human development, and pathogenic germline variants in SETBP1 lead to a recognizable developmental syndrome and variable clinical features. In this study, we assessed a patient with facial dysmorphism, intellectual disability and delayed motor development. Whole genome sequencing identified a novel de novo variation of the SETBP1 (c.2631C>A; p. S877R) gene, which is located in the SKI domain, as a likely pathogenic variant for the proband’s phenotype. RNA sequencing was performed to investigate the potential molecular mechanism of the novel variation in SETBP1. In total, 77 and 38 genes were identified with aberrant expression and splicing, respectively. Moreover, the biological functions of these genes were involved in DNA/protein binding, expression regulation, and the cell cycle, which may advance our understanding of the pathogenesis of SETBP1 in vivo.